AKTIVITAS ANTIBAKTERI MADU TRIGONA TERHADAP BAKTERI GRAM POSITIF (Staphylococcus Aureus) DAN BAKTERI GRAM NEGATIF (Escherichia Coli) - Nur, Astuti (Jurnal Kesehatan Poltekkes Ternate, 2019)
Honey is a natural sweet thick liquid derived from plant nectar commonly known as food and beverage ingredients, also used as a treatment. In this study, South Sulawesi’s trigona honey was tested for antibacterial activity against Staphylococcus aureus and Escherichia coli using agar diffusion method. The proximate analysis showed that the composition of trigona honey consisted of carbohydrates (87.41%), water content (10.90%), fiber content (0.90%), ash content (0.57%), protein content (0.15 %) fat content (0.06%). The average diameter of trigone honey’s inhibition against Eschrichia coli bacteria concentrations of 10%, 20%, 40%, 60%, 80% v / v and positive controls respectively 21.33, 24.67, 27.33, 29.33, 29.67, and 28.67 while those of Staphylococcus aureus bacteria concentrated 10%, 20%, 40%, 60%, 80% v / v and positive controls respectively were 13.67, 15.00, 16.67, 18.00, 19.00, and 21.33. Trigona honey is more effective in inhibiting the growth of Eschrichia coli bacteria than Staphylococcus aureus. The best concentration of trigona honey in inhibiting bacterial growth is 60% -80% because at this concentration is equal to positive control (chloramphenicol). Keywords: Trigona honey,Antibacterial Activity Test, Staphylococcus aureus, Escherichia coli.